Inclusive Communication and the Role of Social Media In Shaping an Equitable Community (Universitas Terbuka, 2025)
Public spaces are becoming increasingly open due to the dynamic development of social media, which allows citizens to communicate freely and equally. However, access gaps, algorithmic bias, and the marginalization of certain groups show that not everyone has the same opportunity to participate. This study highlights the issue of inequality in digital communication and the importance of creating an inclusive space for all groups. The objective of this research is to analyze how inclusive communication is defined and implemented on social media and in digital communities, as well as to evaluate the role of social media in shaping communities that are equitable, inclusive, and participatory. The method used is a literature review relying on a systematic literature review based on a multi-database approach, and tactically developed a combination of keywords relevant to the research topic. The study results indicate that social media platforms have great potential in democratizing participation, amplifying the voices of marginalized groups, and building cross-cultural solidarity. Serious obstacles still exist in the form of the digital divide, algorithmic bias, and experiences of online hostility. Case studies from various platforms show that the success of inclusive communication depends on strategies that are culturally sensitive, community-based, and sustainability-oriented. This research recommends the importance of cross-sector collaboration and the integration of inclusive values into digital platform design, public policy, and organizational communication strategies. These findings are expected to contribute both conceptually and practically to creating a more fair, safe, and representative digital space for all.